Penza's Surgical Maneuver: A Key to Tackle Complex Proximal Descending Thoracic Aortic Infectious or Malignant Issues - Rosseykin, Evgeny; Chichevatov, Dmitry; Sinev, Evgeny; Kobzev, Evgeny (AORTA, 2020)
We performed off-pump ascending-to-descending aortic grafting with the debranching of left carotid and subclavian arteries and total aortic arch transection in three patients. We have called this technique “Penza's Surgical Maneuver” and propose it for a safe surgery in cases where the aortic arch, the aortic isthmus, the beginning segment of the descending aorta, the esophagus, and a lung are diseased.
Keywords: thoracic aorta; cardiopulmonary bypass; vascular surgical procedure; esophagoplasty; thoracic malignancies